(untitled) (Clinics, 2016)
OBJECTIVES: To compare the views of freshman students with senior students of the Faculty of Medicine- University of São Paulo concerning the respect for the mother’s freedom of choice, the need to protect the unborn child, the proportionality between the mother’s freedom of choice and the protection of the unborn child, and issues related to legal abortion. To determine whether the medical knowledge acquired throughout the academic years can influence the views of medical students on these issues. METHODS: First- and sixth-year students of the Faculty of Medicine - University of São Paulo answered a questionnaire; the inclusion criteria were as follows: a first- or sixth-year student of the medical school and a signature on the free informed consent form. To compare the proportions, a chi-square or Fisher’s exact test was used. The significance level was set to 5%. RESULTS: Regarding the mother’s freedom of choice, in the case when a pregnant woman undergoes a cesarean section by means of a court order despite her intention to not have a cesarean, 55.7% of the first-year students have answered that the mother’s choice should be respected. Among the sixth-year students, only 28.9% believe that the mother’s intention should be considered (p